Mercy without borders: the Catholic Worker and immigration - Zwick, Markus (Paulist Press, 2010)
From El Salvador to the Houston Catholic Worker -- Just read the lives of the saints : Casa Juan Diego begins -- Why Juan Diego? a saint for nobodies -- Can the works of mercy be illegal? -- Casa Juan Diego rises from the ashes -- Oh, freedom! -- God will say, "where are the others?" -- "Love in action is a harsh and dreadful thing" -- Escaping violence, only to find it again -- Their bones will rise again -- Deportation is a sin -- Christ did not die for profit -- Angel's story : "I almost suffocated in the trailer" -- Afterword : "how did you get that way?" -- Appendix 1 : FAQs: the truth about Casa Juan Diego -- Appendix 2 : houses of hospitality (albergues) in Mexico and Guatemala